2013
DOI: 10.1016/j.ajhg.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Germline BAP1 Mutations Predispose to Renal Cell Carcinomas

Abstract: The genetic cause of some familial nonsyndromic renal cell carcinomas (RCC) defined by at least two affected first-degree relatives is unknown. By combining whole-exome sequencing and tumor profiling in a family prone to cases of RCC, we identified a germline BAP1 mutation c.277A>G (p.Thr93Ala) as the probable genetic basis of RCC predisposition. This mutation segregated with all four RCC-affected relatives. Furthermore, BAP1 was found to be inactivated in RCC-affected individuals from this family. No BAP1 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
189
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(208 citation statements)
references
References 28 publications
9
189
0
7
Order By: Relevance
“…IHC findings in three epithelioid MM cases (C-II-1, D-II-3, O-II-3) suggest that the loss of nuclear staining occurred via somatic mutation Page 10 of 19 (see Figure 1). BAP1 nuclear staining retained in one sarcomatoid MM (G-II-8) is in agreement with other studies reporting data of positive BAP1 staining on sarcomatoid MM [25] and on the absence of BAP1 mutation [9,10,18,19]. Considering all families with multiple cases of MM analyzed to date for BAP1 germline mutations (see Table 2), those described in the present study without a predisposing germline BAP1 mutation are similar to those reported by other investigators [9,10,19].…”
Section: Case D-ii-3) Somatic Mutations In Exonsupporting
confidence: 82%
See 4 more Smart Citations
“…IHC findings in three epithelioid MM cases (C-II-1, D-II-3, O-II-3) suggest that the loss of nuclear staining occurred via somatic mutation Page 10 of 19 (see Figure 1). BAP1 nuclear staining retained in one sarcomatoid MM (G-II-8) is in agreement with other studies reporting data of positive BAP1 staining on sarcomatoid MM [25] and on the absence of BAP1 mutation [9,10,18,19]. Considering all families with multiple cases of MM analyzed to date for BAP1 germline mutations (see Table 2), those described in the present study without a predisposing germline BAP1 mutation are similar to those reported by other investigators [9,10,19].…”
Section: Case D-ii-3) Somatic Mutations In Exonsupporting
confidence: 82%
“…We cannot exclude large deletions of BAP1 that are undetectable by Sanger sequencing [3,9,11,19]. However, large deletions of BAP1 have never been detected in germline configuration in families either with multiple MM [3,9,11,[32][33][34][35][36][37] or without MM [26,28,29]. The loss of nuclear BAP1 immunostaining suggests that these tumors may harbor somatic alterations of the BAP1 gene, a frequent event in sporadic epithelial MM [21,24,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations